PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN NILAI-NILAI KARAKTER SISWA KELAS X TKJ SMK TELKOM PEKANBARU - Doriaman '; Rosmawati '; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of group counseling services to the increasing values of character class X TKJ SMK Telkom Pekanbaru. The method used is the method of true experimental design with a pattern of pretest-posttest control group design. Which is the subject in the study were a number of students of class X TKJ SMK Telkom Pekanbaru totaling 20 of 10 students for the experimental group and 10 students for the control group, subjects were selected by purposive sampling in accordance with the characteristics of the subject to be studied is that has a level practice the values of the lowest character. Data processed by nonparametric statistics with the help of SPSS version 16. The significance value smaller than α (0.004<0.05), which means that there are significant differences in pre-test with pot-test for the experimental group. For the control group there was no difference of pre-test to post-test for significance value greater than α (0.282>0.05). The result of the calculation of the data U test experimental group and the control group, while the significance value smaller than α (0.000<0.05) means that there are significant differences between the groups of experimentation with the control group. From the calculation of rank correlation spearment known Koofesien Determinant or r2 = 0.55 which means there is a 55% contribution to the improvement of counseling services group practice of the values of character class X SMK Telkom Pekanbaru in the academic year 2015/2016.Key Words: Effect, Group Guidance, Values Character